Swedish version of the Pregnancy Physical Activity Questionnaire (PPAQ-SWE), translation and cultural adaptation - Annika Svahn Ekdahl; Viana Mikkelsen; Heléna Frenell; Qarin Lood; Theresa Westgård; Joanne M. Fuller; Andrea Mikkelsen; Annelie Gutke (BMC Research Notes)
Abstract Objective Physical activity has well-known health benefits in all stages of life and may also reduce the risk for pregnancy-related complications, but many pregnant women do not reach the recommended activity levels. Tailored advice is often provided by healthcare professionals to promote physical activity during pregnancy. To provide such advice, assessment of the actual level of physical activity is necessary, but there are currently no standardized methods for this. The Pregnancy Physical Activity Questionnaire (PPAQ) is a self-administered instrument, designed to determine physical activity during pregnancy but a Swedish version of the questionnaire is not yet available. Result The PPAQ was translated and culturally adapted into a Swedish version, i.e., PPAQ-SWE according to the process described by Beaton et al. Several minor linguistic adjustments were needed, that mainly concerned semantic and cultural adaptations, such as adding, removing, or replacing words to match Swedish cultural aspects. For instance, “gestational week” was used instead of “trimester,” and “older person” replaced “older adult.” The reference to a “1-gallon milk jug” was replaced with “3–4 liters of milk” to fit the metric system used in Sweden. Two questions regarding bicycling, a common form of transportation in Sweden, and one free-text comment option was added.